2019
DOI: 10.1038/s41598-019-42229-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Design of JOC-x, a Conjugatable Tumor Tight Junction Opener to Enhance Cancer Therapy

Abstract: Disorganized intercellular junctions are critical for maintaining the integrity of solid epithelial tumors and prevent the infiltration of oncological therapies into the bulk of the malignancy. We have developed small, recombinant proteins which bind a critical junction protein, desmoglein 2, triggering the transient and specific opening of tumor tight junctions allowing for infiltration of the tumor with immune cells, oncolytic viruses, drugs, and other therapeutics. Our new molecule, JOC- x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The therapeutic efficacy of anticancer drugs in solid tumors depends on the drug’s penetration into the tumor mass, affinity to the target, and retention at the site of action (Moradi Kashkooli et al., 2021 ). Epithelial cancers are characterized by tight junctions (TJs) that create obstacles to naturally occurring immune cells, antibodies, and drug therapies (Pitner et al., 2019 ). Studies have revealed a positive correlation between the upregulation of TJ proteins in solid tumors and their resistance to drug therapy (Martin, 2014 ; Pitner et al., 2019 ).…”
Section: Approaches For Enhancing Intracellular Delivery Of Anticance...mentioning
confidence: 99%
See 2 more Smart Citations
“…The therapeutic efficacy of anticancer drugs in solid tumors depends on the drug’s penetration into the tumor mass, affinity to the target, and retention at the site of action (Moradi Kashkooli et al., 2021 ). Epithelial cancers are characterized by tight junctions (TJs) that create obstacles to naturally occurring immune cells, antibodies, and drug therapies (Pitner et al., 2019 ). Studies have revealed a positive correlation between the upregulation of TJ proteins in solid tumors and their resistance to drug therapy (Martin, 2014 ; Pitner et al., 2019 ).…”
Section: Approaches For Enhancing Intracellular Delivery Of Anticance...mentioning
confidence: 99%
“…Epithelial cancers are characterized by tight junctions (TJs) that create obstacles to naturally occurring immune cells, antibodies, and drug therapies (Pitner et al., 2019 ). Studies have revealed a positive correlation between the upregulation of TJ proteins in solid tumors and their resistance to drug therapy (Martin, 2014 ; Pitner et al., 2019 ). The primary function of TJs is to mediate intercellular adhesion and polarity.…”
Section: Approaches For Enhancing Intracellular Delivery Of Anticance...mentioning
confidence: 99%
See 1 more Smart Citation
“…ZnPP PM loaded by poly-IC could activate T lymphocytes and NK cells, and effectively repolarize TAM in B16-F10 melanoma tumor model. JOC-x is a conjugatable tumor tight junction opener, when conjugated with poly-IC, it could not only recruit and activate of CD8 + T cells by targeting DCs, but also play a tumor killing role by initiating apoptosis in tumor cells [ 133 ].…”
Section: Rna Sensors In Cancer Immunotherapymentioning
confidence: 99%
“…The V239D mutation is localized in a region of the knob corresponding to an exposed loop (E-F). As this region is located at the side of the fiber knob, it is not a direct binding region to DSG2, but it is known to be critical for stabilizing DSG2 binding [23,24]. Notably, only part of the residues critical for Ad3 fiber knob binding to DSG2 are conserved in the other DSG2-interacting adenoviruses (Ad7, Ad11, Ad14 and Ad55).…”
Section: Introductionmentioning
confidence: 99%